50.9k views
5 votes
Which is the value of this expression when p=-2 and q=-1?

A. -4

B. -1/16

C. 1/16

D. 4

Which is the value of this expression when p=-2 and q=-1? A. -4 B. -1/16 C. 1/16 D-example-1
User Aevitas
by
5.2k points

1 Answer

3 votes

Answer:

D. 4

Explanation:


[(p^2) (q^(-3)) ]^(-2).[(p)^(-3)(q)^5] ^(-2)\\\\</p><p></p><p>=[(p^2) (q^(-3)) *(p)^(-3)(q)^5 ]^(-2)\\\\</p><p></p><p>=[(p^(2)) *(p)^(-3) * (q^(-3)) *(q)^5 ]^(-2)\\\\</p><p></p><p>=[(p^(2-3)) * (q^(5-3)) ]^(-2)\\\\</p><p></p><p>=[(p^(-1)) * (q^(2)) ]^(-2)\\\\</p><p></p><p>=(p^(-1* (-2))) * (q^(2* (-2) )) \\\\</p><p></p><p>=p^(2)* q^(-4) \\\\</p><p></p><p>= (p^2)/(q^4)\\\\</p><p></p><p>= ((-2)^2)/((-1)^4)\\\\</p><p></p><p>= (4)/(1)\\\\</p><p></p><p>= 4

User Mike Roosa
by
5.3k points